2007
DOI: 10.1158/0008-5472.can-07-0380
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 Short Interfering RNA Induced Senescence Resulting in Inhibition of Medulloblastoma Growth via p16INK4a and Mitogen-Activated Protein Kinase Pathway

Abstract: The involvement of matrix metalloproteinases (MMP) has been suggested in cellular mechanisms leading to medulloblastoma, the most common malignant brain tumor in children. A significant association of the expression levels of MMP-9 with survival and M stage suggests that patients with medulloblastoma metastatic disease at diagnosis may benefit from the anti-MMP therapy. Here, we have evaluated the tumorigenicity of medulloblastoma cells after infection with an adenovirus containing a 21-bp short interfering RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 47 publications
0
41
1
1
Order By: Relevance
“…Both TIMP-1 and MMP-9 play an important role in cellular senescence, proliferation, and apoptosis, which are the pivotal contributing factors in driving the progression of COPD/emphysema (1,13,27,30,37,38,42,45,49). This provides a possibility that the protection against experimental emphysema by SIRT1 is due to reduced cellular senescence and apoptosis via redressing of TIMP-1/MMP-9 imbalance in mouse lungs by a mechanism involving dampening the senescence-associated secretory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Both TIMP-1 and MMP-9 play an important role in cellular senescence, proliferation, and apoptosis, which are the pivotal contributing factors in driving the progression of COPD/emphysema (1,13,27,30,37,38,42,45,49). This provides a possibility that the protection against experimental emphysema by SIRT1 is due to reduced cellular senescence and apoptosis via redressing of TIMP-1/MMP-9 imbalance in mouse lungs by a mechanism involving dampening the senescence-associated secretory phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that silencing MMP-9 is an effective method for the treatment of ovarian cancer. MMP-9 is one of the most important metalloproteases and is critical in regulating ECM dissolution, activating growth factors as well as initiating intracellular signaling leading to tumor progression and metastasis (26)(27)(28)(29). Several studies have demonstrated that inhibiting the activities of MMP-9 by RNAi resulted in apoptosis in melanoma cells (15), malignant meningioma cells (27) and medulloblastoma cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Short interfering RNA (siRNA) was recently shown to be an effective method for inhibiting the expression of a specific gene in human cells, and current published data suggest antitumor potential effects of this technique (Tong et al, 2005). Indeed, a siRNA sequence of human MMP-9 was shown to inhibit medulloblastoma cell growth and invasion both in vitro and in vivo (Rao et al, 2007). Furthermore, simultaneous downregulation of uPAR and MMP-9 expression by means of RNA interference dramatically reduced glioblastoma growth, invasion, and angiogenesis in both in vitro and in vivo models (Lakka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%